A Comparison of Experienced and Inexeperienced Auditors: The Role of Feedback on Internal Control Assesments - YAVIDA NURIM (The Indonesian Journal of Accounting Research, 2013)
Internal control task has a significant role in the overall process of an audit because it determines the scope of the auditor's examination. Therefore, auditors' competence as a result of obtaining experience will optimize the performance on internal control judgment. However, internal control as structured tasks which needs little judgment or experience has a rich learning environment. Therefore, it can be acquired through learning by doing as learning theory states that subjects who receive feedback after completing tasks will acquire knowledge which can only be acquired by professional auditors. This study uses experimental methods with students as participant and   survey methods with experienced auditors as participants. The findings show that subjects who receive feedback after the task completion have higher internal control performance rather than subjects who do not receive any feedback. The findings also show that an outcome feedback is more appropriate to facilitate learning than an explanatory feedback. Findings also show that experience auditors have lower internal control performance than inexperienced auditors who receive feedback after task completion. The results are consistent with prior research that internal control tasksare structured tasks. Due to such a characteristic, internal control task can be acquired through learning by doing as suggested by learning theory.